[Street Scene in Húsavík] - Streng, Evelyn Fiedler (1975)
Photograph of a street scene at Húsavík, Iceland. A white church lined with brown trimming and a green roof sits along the sidewalk to the left of a brown building with a green roof in the foreground. White fences line the edge of the sidewalk beside the buildings. A rectangular building is visible in the background to the left, a sign in Icelandic along the top of it. A group of people walk along the sidewalk to the left.